Departmental Fights: Finding Solutions and Maintaining Sanity as Chair - Ethan W Krase; Gian S Pagnucci (Academic Chairpersons Conference Proceedings, 2017)
While circumstances of departmental conflicts are variable, one constant is that as chairs we end up involved. Although chairs cannot prevent conflict from occurring, there are steps we can take to minimize the consequences. This session offers strategies chairs can use to lead their departments through conflict more productively.
Keywords: • conflict • personnel • leadership • management • dispute resolution